Pott's disease: a case of Mycobacterium xenopi infection of the spine - Majd Alfreijat; Chiagozie Ononiwu; Carlton Sexton (Greater Baltimore Medical Center, 2013)
Pott's disease is an infection of the spine with Mycobacterium tuberculosis that causes destruction of the spine elements resulting in progressive kyphosis. We are describing a rare case of Pott's disease where Mycobacterium xenopi was the inculpated organism.